1978
DOI: 10.1128/jvi.27.3.551-559.1978
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mouse mammary tumor virus in spontaneous and hormone-induced mammary tumors in low-mammary-tumor mouse strains

Abstract: The involvement of the mouse mammary tumor virus (MTV) in spontaneous and hormone-induced mammary tumors in low-mammary-tumor mouse strains was studied by comparing the amounts of MTV RNA and MTV DNA sequences in mammary tumors and other tissues of mice with an without hormonal treatments. The following results were obtained. (i) Mammary tumors which appeared in C3H mice as a result of an infection with MTV contained more MTV DNA compared with noninfected organs; these mammary tumors also contained more MTV RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
0

Year Published

1979
1979
1981
1981

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
6
30
0
Order By: Relevance
“…Treatment with either 1 ng DMBA or 1 pg FAA at days 3 to 4 had apparently no effect on this level. This value is comparable to the previously reported amounts of MuMTV RNA in the mammary glands of BALB/c mice (Varmus et al, 1973;Michalides et al, 1978a;Dudley et al, 19786;Long et al, 1980). A set of RNA hybridization curves is shown in Figure 2u.…”
Section: Mumtv Rna Levels In Carcinogen-treated Mammary Glandssupporting
confidence: 89%
See 2 more Smart Citations
“…Treatment with either 1 ng DMBA or 1 pg FAA at days 3 to 4 had apparently no effect on this level. This value is comparable to the previously reported amounts of MuMTV RNA in the mammary glands of BALB/c mice (Varmus et al, 1973;Michalides et al, 1978a;Dudley et al, 19786;Long et al, 1980). A set of RNA hybridization curves is shown in Figure 2u.…”
Section: Mumtv Rna Levels In Carcinogen-treated Mammary Glandssupporting
confidence: 89%
“…The mammary glands of BALB/c mice have barely detectable levels of endogenous MuMTV RNA in vivo (Varmus et al, 1973;Michalides et al, 1978a;Dudley et al, 1978b;Long et al, 1980). Using the whole-organ culture system, we therefore undertook to determine if elevations in the steady-state levels of MuMTV RNA and protein result from the treatment of the mammary glands with either of the two chemical carcinogens, DMBA or FAA.…”
Section: Mumtv Rna Levels In Carcinogen-treated Mammary Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular hybridization procedures have been employed in several laboratories to determine the number of MuMTV DNA and MuMTV RNA copies per cell in various mouse tissues. Many studies (Drohan et al, 1977;Michalides et al, 1976;Morris et al, 1977;and Varmus et al, 1973) have shown that virus-induced mammary tumors such as those that occur in RIII, C3H, A, and BALB/cfC3H mice contain higher amounts of both MuMTV DNA and MuMTV RNA sequences than those found in other body tissues. However, Varmus ef al.…”
Section: Discussionmentioning
confidence: 99%
“…These examples, in addition to the findings of this report, emphasize the effect of genetic differences among mouse strains on the occurrence of mammary carcinoma and the differences in the etiology of the disease in mic; and in humans. In most mammary tumors in the mouse, MuMTV is an important etiological factor, but there is evidence that in some strains mammary tumors can occur without additional MuMTV expression (Michalides et a/., 1978;Moore ef al., 1979). In an occasional feral mouse, even the MuMTV genome is missing (Cohen and Varmus, 1979).…”
Section: Discussionmentioning
confidence: 99%